2021
DOI: 10.1038/s41598-021-89359-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world rogue wave probabilities

Abstract: Rogue waves are dangerous ocean waves at least twice as high as the surrounding waves. Despite an abundance of studies conducting simulations or wave tank experiments, there is so far no reliable forecast for them. In this study, we use data mining and interpretable machine learning to analyze large amounts of observational data instead (more than 1 billion waves). This reveals how rogue wave occurrence depends on the sea state. We find that traditionally favored parameters such as surface elevation kurtosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
6
29
1
Order By: Relevance
“…whether the rogue wave definition by a certain height or crest threshold is useful in practice (Häfner et al, 2021). Several authors have, based on large measurement datasets, come to the conclusion that these rogue waves are rare, but nevertheless realisations of commonly used wave distributions (e.g., Waseda et al, 2011;Christou and Ewans, 2014).…”
mentioning
confidence: 99%
“…whether the rogue wave definition by a certain height or crest threshold is useful in practice (Häfner et al, 2021). Several authors have, based on large measurement datasets, come to the conclusion that these rogue waves are rare, but nevertheless realisations of commonly used wave distributions (e.g., Waseda et al, 2011;Christou and Ewans, 2014).…”
mentioning
confidence: 99%
“…Most recent findings by Häfner et al (2021b) revealed, based on machine learning algorithms applied to Coastal Data Information Program (CDIP) buoy data from the US coast with > 1 m, that the spectral bandwidth ( and ) provides some information on the probability of rogue waves according to the height criterion. Furthermore, their study revealed that bandwidth effects are not relevant for wave crests.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our measurement data, we can confirm these results: although we observed slightly higher bandwidths than usual in crest rogue wave time series, these differences showed to be statistically insignificant. The CDIP data set includes data from water depths between aproximately 10 and 4,500 m. Häfner et al (2021b) supposed that the influence of second-order nonlinearities on wave crests might be higher than estimated on the basis of buoy measurement data. Wave buoys tend to cancel second-order nonlinearities by their own Lagrangian movement and thus to overestimate the mean water level, which in turn leads to an underestimation of crest heights (Forristall 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ measurements play an important role in the investigation of the characteristics and frequencies of the appearance of rogue waves in nature. Such in situ wave measurements are carried out in different locations of World Ocean, for example (Didenkulova and Anderson, 2010;Mori et al, 2002;Stansell, 2004;Christou and Ewans, 2014;Häfner et al, 2021). However, their amount and locations of measurements are limited.…”
mentioning
confidence: 99%